Devolvement of HR practices in transitional economies: evidence from China - Zhu, Cherrie Jiuhua; Cooper, Brian; Cieri, Helen De; Thomson, Stanley Bruce; Zhao, Shuming (My University, 2008)
China's progressive integration into the global economy has strengthened its position as a ‘magnet’ for foreign direct investment. The inevitably increased competition in the Chinese economy has led firms to adopt more market-oriented approaches to human resource management (HRM). Based on a survey of 618 managers in state-owned enterprises, domestic/private- and foreign-invested firms operating in the Jiangsu Province of China, this study investigates the extent to which HR practices have been strategically devolved to line managers, and the relationship between this devolvement and the performance of firms in China. Overall, there was little evidence of devolvement to line managers. We found no evidence of a relationship between the degree of devolvement and firm performance, although the provision of formal training to line/middle managers was predictive of performance.
Keywords: China; devolvement; firms; HR practices; line/middle management; performance